Intermetallic semiconducting films - Wieder, H. H., 1919- (International series of monographs on semiconductors, 1970)
Intermetallic Semiconducting Films introduces the physics and technology of A??v compound films. This material is a type of a polycrystalline semiconductor that is used for galvanomagnetic device applications. Such material has a high electron mobility that is ideal for generators and magnetoresistors.